Manipulation of source-to-sink ratios in girdled coffee branches evidences lack of photosynthetic down-regulation: the interplay of photosynthesis with respiration and photorespiration pathways and amino acid metabolism - Avila, Rodrigo Teixeira (2016)
We aimed to gain a better understanding on how the regulation of photosynthesis in coffee depends on sink activity or carbohydrate build-up in source leaves and how the coffee tree adjusts its photosynthetic performance and primary metabolism to varying source-to-sink ratios. For these purposes, we use integrative approaches combining gas- exchange and chlorophyll a fluorescence measurements, analyses of carbohydrates and major metabolites, activities of a range of enzymes and the expression of some genes encoding for key enzymes of the carbon metabolism to achieve a holistic view of the whole leaf metabolism in response to long-term source-to-sink manipulation. We designed a field experiment by girdling coffee branches that were further manipulated by controlled defoliation and/or defruiting so that three highly varying source-to-sink ratios were created. We found that under remarkably high source-to-sink ratios photosynthesis rates were chiefly limited by diffusive factors (that were apparently unrelated to whole-leaf abscisic acid) with no apparent signs of feedback down- regulation. Lack of down-regulation was associated with an enormous capacity for starch accumulation coupled with maintenance of low levels of soluble sugars. Chronic Chronic photoinhibition and photodamage could be avoided through adjustments in leaf photochemistry, photorespiration and respiration amongst other processes. No major metabolic reprograming was found at the level of key enzymes associated with carbon metabolism. Metabolic adjustments in source leaves were more evident under high-sink demand conditions and centered more on nitrogen metabolism than on carbon metabolism. In conclusion, our results offer novel insights on the high coordination between the source supply and sink demand in coffee trees, with no evident signs of photosynthetic down-regulation even under dramatically low-sink conditions.